The Korean Heart Study: rationale, objectives, protocol, and preliminary results for a new prospective cohort study of 430, 920 men and women. (29th August 2020) - Jee, Sun Ha; Batty, G David; Jang, Yangsoo; Oh, Dong Joo; Oh, Byung-Hee; Lee, Sang Hoon; Park, Seong-Wook; Seung, Ki-Bae; Kimm, Heejin; Kim, Sang Yeun; Mok, Yejin; Kim, Hyon-Suk; et al.
Abstract: Background: To describe the rationale, objectives, protocol, and preliminary results for a new prospective cohort study of cardiovascular disease (CVD) risk factors in South Korea. Methods: Study members were recruited from participants in routine health assessments at health promotion centres across South Korea. Established and emerging CVD risk factors were measured. Eighteen centres holding electronic health records agreed to linkage of participants' records to future health insurance claims for monitoring of disease events. The recruitment of 430, 920 participants (266, 782 men, 164, 138 women), aged 30–74 years, provides broad geographical reach across South Korea. Results: Risk factor prevalence was more favourable in women than men, and, in general, in the younger rather than older study members. There was also close similarity between the characteristics of the present sample and the Korean National Health and Nutrition Examination Survey. The expected associations between risk factors and both CVD and death were also apparent. Conclusions: Data from the present sample, based on data linkage, show close agreement with South Korea-wide surveys (for risk factor prevalence) and the extant literature (for risk factor associations). These findings gives confidence in future results anticipated from this cohort study of east Asians – a group that has been traditionally under-researched.